Population Characteristics of Feral Horses Impacted by Anthropogenic Factors and Their Management Implications - Mendonça, Renata S.; Pinto, Pandora; Maeda, Tamao; Inoue, Sota; Ringhofer, Monamie; Yamamoto, Shinya; Hirata, Satoshi (Frontiers in Ecology and Evolution, 2022)
Feral horses form relatively stable harems over time that are characterized by long-lasting bonds among their members, a characteristic that makes them an exceptional case of a social system among terrestrial ungulates. Their social system has been described as uniform despite the wide differences in their environment and demography. Horse populations subjected to human interference often show higher levels of population instability that can ultimately compromise their reproductive success. In this article, we describe demographic and dynamic changes of a Portuguese population of Garranos in Serra d’Arga (SA), which is impacted by human and predation pressures, over six breeding seasons. Furthermore, we tested several hypotheses related to the impact of anthropogenic disturbance on the structure and dynamics of this population. Our results revealed that the SA population had relatively little human interference at the start of the project in 2016. This was supported by the natural composition of the herd (total number of individuals, 206), which consisted of several single- and multi-male harems (n = 17 and 7, respectively) and bachelor males (n = 9). However, from 2017 to 2021, SA’s Garrano population suffered a drastic decline. Approximately two-thirds of the individuals and all bachelor males disappeared, and 76% of adult female transfers occurred after the death or disappearance of the harem male. Predatory pressures and poor management of the population, which allowed illegal human interference, contributed to this population crisis. A low population growth rate, reduced birth and foal survival rates, in addition to a delayed primiparous age were observed in this population and exacerbated after its drastic decline; suggesting the viability and survival of this Garrano population were compromised. Investigating the population demographic changes and their causes and consequences can provide guidelines for managing populations and help fight the extinction of horse breeds.